ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN LINDUNG NILAI (HEDGING). (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2010-2014) - Egi Slastio Manova; Errin Yani Wijaya; Andewi Rokhmawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to analyzed the influence of Growth Opportunity, Leverage, Firm Size, Current Ratio, and Financial Distress to Hedging decision. The population in this research were 41 companies of mining company listed in Indonesia Stock Exchange period 2010-2014. The sampling method is purposive sampling. Sample of the research consists of 29 companies multiplied by five years, so the observation in this research were 145 observations. Analysis method that use is descriptive analysis with logistic regression model were prossed by SPSS version 21.00. The result showed that the variables direcly effect to hedging decision are Leverage and Firm size. Meanwhile, Growth opportunity, Current ratio, and Financial distress does no effect indirectly to Hedging decision. The management of companies should do hedging decision on foreign currency of derivative instruments to protect the company from their exposure transaction. For investors who want to invest in mining companies that have exposure transactions more attention of Growth opportunity, Leverage, Firm size, Current ratio, and Financial distress to choose which company have can protect their asset from fluctuations the foreign currency exchange risk.Keyword : Growth Opportunity, Leverage, Firm Size, Current Ratio, Financial Distress, Hedging